2008
DOI: 10.4088/jcp.v69n0420
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Treatment of Postpartum Women With New-Onset Major Depressive Disorder

Abstract: Study results were limited by lower than expected enrollment and higher than anticipated attrition. Nonetheless, paroxetine treatment was associated with a significantly higher rate of remission among women with postpartum onset of MDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 24 publications
0
90
1
Order By: Relevance
“…Paroxetine hydrochloride is one of the most potent inhibitors of the reuptake of serotonin (5-hydroxytryptamine ) of all the currently available antidepressants including the class of SSRIs with currently approved indications for the treatment of depression, obsessive-compulsive disorder, panic disorder, and social anxiety (Anderson 2000;Ballus et al 2000;Bourin et al 2001;Chaudhry et al 2002;Claghorn et al 1992;Emslie et al 2006;Danish University Antidepressant Group 1990;Keller et al 2001;Nemeroff 1993;Rapaport et al 2003;Yonkers et al 2008). It is also used in the treatment of generalized anxiety disorder, post-traumatic stress disorder, premenstrual dysphoric disorder, and chronic headache .…”
Section: Introductionmentioning
confidence: 98%
“…Paroxetine hydrochloride is one of the most potent inhibitors of the reuptake of serotonin (5-hydroxytryptamine ) of all the currently available antidepressants including the class of SSRIs with currently approved indications for the treatment of depression, obsessive-compulsive disorder, panic disorder, and social anxiety (Anderson 2000;Ballus et al 2000;Bourin et al 2001;Chaudhry et al 2002;Claghorn et al 1992;Emslie et al 2006;Danish University Antidepressant Group 1990;Keller et al 2001;Nemeroff 1993;Rapaport et al 2003;Yonkers et al 2008). It is also used in the treatment of generalized anxiety disorder, post-traumatic stress disorder, premenstrual dysphoric disorder, and chronic headache .…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, paroxetine was evaluated in an 8 weeks randomized controlled trial against placebo. This study also showed better remission rate with paroxetine (Yonkers et al 2008). However, most of these studies involved sample size of less than 100 indicating reliability to be obtained from larger randomized controlled trials.…”
Section: Selective Serotonin Reuptake Inhibitors (Ssri):-mentioning
confidence: 93%
“…34 Nonetheless, there is evidence supporting pharmacologic and other biological interventions (for example, hormonal interventions or bright light therapy) for the treatment of moderate-to-severe depression in postpartum women. 35,36 While few placebo-controlled trials of ADs have been conducted in women with PPD, 2 trials have yielded positive results, 37,38 and ADs appear to be as effective for PPD as for MDD occurring at other times in the life cycle. 36 However, concerns have been raised regarding the robustness of evidence on which these conclusions are based, 35 and few studies have compared different classes of medications for the treatment of PPD.…”
Section: Treatment Of Ppdmentioning
confidence: 99%